Corn wireworm Melanotus communis Gyllenhal (Insecta: Coleoptera: Elateridae) - Harsimran K. Gill; Gurminder Chahil; Gaurav Goyal; Jennifer L. Gillett-Kaufman; Ronald Cherry (EDIS, 2014)
Insects in the family Elateridae are commonly known as click beetles. Their name comes from the clicking sound they make while attempting to right themselves after falling or being placed on their backs. The larvae of click beetles are called wireworms. The corn wireworm is a serious agricultural pest and was added to the EPPO A1 action list of quarantine pests in 2002. This 6-page fact sheet was written by Harsimran K. Gill, Gurminder Chahil, Gaurav Goyal, Jennifer L. Gillett-Kaufman, and Ronald Cherry, and published by the UF Department of Entomology and Nematology, January 2014.